Enhanced Selectivity of Ni/Al LDH for Cationic Dye Adsorption via Gambier Leaf Extract Modification - Jefri, Jefri; Fithri, Najma Annuria; Ramadhan, Navinda (Indonesian Journal of Material Research, 2025)
The adsorption capability of Ni/Al LDH modified with gambier leaf extract was evaluated for the removal of Rhodamine B (RhB), Malachite Green (MG), and Methylene Blue (MB) dyes from aqueous solutions. UV-Vis spectroscopy analysis revealed that Ni/Al-Gambier Leaf Extract exhibited a higher efficiency in cationic dye removal compared to unmodified Ni/Al LDH. The removal percentages of RhB, MG, and MB using unmodified Ni/Al LDH were 6.00%, 40.05%, and 14.73%, respectively. However, after modification with Gambier Leaf Extract, these values significantly improved to 25.62%, 39.48%, and 31.06%, respectively. This enhancement was attributed to the polyphenolic functional groups present in the gambier leaf extract, which strengthened electrostatic interactions and promoted dye adsorption. These findings indicate that incorporating gambier leaf extract into Ni/Al LDH enhances its adsorption performance, making it a promising material for improving dye removal in wastewater treatment.